MAKNA AMBATIK – PALMERAH - Indra Lesmana; Petrus Rudi Kasimun (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
The existence of an open space, is truly important to nowadays urban society. Because basically, community of a city has been bounded to open spaces around that city. The need of a thirdplace in a city, now, is way more than just a regular, it became a lifestyle. This thirdplace phenomena give impacts to the usage of outdoor spaces in the city which used to be indoor spaces, now became outdoor ones (public areas). What used to be a mall and a café that are favorites, now turning into outdoor spaces such as parks, streets (pedestrians), public spaces for children, recreation areas, and so on. Jakarta, especially in Palmerah, open spaces are very rarely  found. In the other side, Palmerah used to be known for its batik, but now it’s already all  gone. Batik as the main program that supports this thirdplace is expected to be able to accommodate the work or activities of local residents. Hold on to Ray Oldenburg’s theory about the third place criteria, batik in this design is intended as a medium for local residents to meet, greet, and interact. With this, batik media is able to accommodate the need of a thirdplace itself. However  still, open spaces in this design has the largest percentage as public spaces for local residents to do some activities and interactions. Batik phases are realized in creating existing spaces; starting from seeing, then feeling, and finally doing. Batik produced by locals can be resold and later become their income. Plots of spaces, materials, wall tears, and batik carvings are also highlighted in this building to create characteristic of this Ambatik building. With Ambatik, all ages, all genders, all types of ethnicity, culture, and race, can be united without any difference.AbstrakKeberadaan ruang luar sangatlah penting bagi masyarakat kota saat ini. Pada dasarnya, masyarakat memiliki keterikatan pada ruang-ruang terbuka kota. Sekarang, Kebutuhan tempat ketiga di dalam suatu kota sudah lebih dari sekedar kebutuhan biasa, tetapi sudah menjadi gaya hidup. Fenomena tempat ketiga berdampak pada penggunaan ruang luar yang pada awalnya dari penggunaan ruang dalam, mulai beralih ke ruang luar (ruang publik). Yang semula mall dan kafe menjadi ruang favorit, sekarang beralih ke ruang luar publik seperti taman, jalan (pedestrian), RPTRA, tempat rekreasi dan sebagainya. Di Jakarta, tepatnya di Palmerah, ruang-ruang terbuka bagi warga sekitar sangatlah jarang ditemui. Di satu sisi, Palmerah yang dalam sejarah dikenal oleh batiknya, sekarang sudah menghilang. Ambatik hadir untuk menunjang tempat ketiga di kawasan Palmerah, yang diharapkan mampu mewadahi kegiatan ataupun aktivitas dari warga sekitar, sekaligus menghidupkan kembali identitas batik di Palmerah. Dengan teori Ray Oldenburg mengenai kriteria sebuah tempat ketiga, batik dalam rancangan ini dimaksudkan sebagai media bagi warga sekitar untuk bertemu, bersapa dan berinteraksi. Ruang-ruang terbuka dalam rancangan ini juga berguna sebagai ruang publik bagi warga sekitar untuk beraktivitas, berinteraksi untuk melakukan kegiatan seni dan budaya. Fase-fase batik juga diwujudkan dalam menciptakan ruang-ruang yang ada, mulai dari melihat, kemudian merasakan, dan melakukan. Dengan hadirnya Ambatik, diharap mampu meningkatkan relasi antar warga, pemahaman baru tentang batik, dan kesadaran akan tradisi.